Flowering, fruit set and fruit development - Cho, Joanna Lee Ying; Ding, Phebe (CAB International, 2024)
This chapter explores flowering stimulation, floral morphology, pollination and fertilization processes for dragon fruit plants, and the development of fruit. Flowering in dragon fruit is influenced by shoot age, temperature, and light quantity.